2005
DOI: 10.1037/0735-7028.36.6.681
|View full text |Cite
|
Sign up to set email alerts
|

Psychology Students' Training in the Management of Potentially Violent Clients.

Abstract: Client violence has been reported as one of student practitioners' greatest concerns. This study examined counseling and clinical psychology graduate students' exposure to client violence, perceptions of training received in managing potentially violent clients, and confidence in working with this population. Students reported that their training in the management of potentially violent clients was inadequate and that their confidence in working with this population was low. A positive correlation between perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
0
20
0
1
Order By: Relevance
“…These authors outlined five factors related to effective countertransference management: self-insight, selfintegration, anxiety management, empathy, and conceptualizing ability. Given the data presented by Pope and Tabachnick (1993) and Gately and Stabb (2005), just outlined, how to most effectively and appropriately respond to client violence, or fear of potential client violence, is an area of great importance for psychotherapists.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…These authors outlined five factors related to effective countertransference management: self-insight, selfintegration, anxiety management, empathy, and conceptualizing ability. Given the data presented by Pope and Tabachnick (1993) and Gately and Stabb (2005), just outlined, how to most effectively and appropriately respond to client violence, or fear of potential client violence, is an area of great importance for psychotherapists.…”
mentioning
confidence: 98%
“…A very small percentage (3.2%) had even gone to the extreme of obtaining a weapon to protect themselves against a possible attack from a client, and an even smaller percentage (0.4%) had actually used a weapon to protect themselves against an attack from a client. Gately and Stabb (2005) addressed the issue of violence experienced by mental health professionals. They cited data to illustrate that this is not an uncommon occurrence and that 35 to 40% of psychologists in clinical practice are at risk of being assaulted by a client at some point.…”
mentioning
confidence: 99%
“…Although this includes postincident actions of reporting, investigation and counseling, simply focusing upon identifying and reducing the risk of being attacked may not be adequate (Gately & Stabb, 2005). Findings suggested that participants find their professional role undermined as a result of client violence targeted towards them and while support for psychologists who have experienced client violence is usually provided by their employers, professional regulatory bodies have a part to play in bringing forward the realities of client violence and raising its profile as a pertinent issue for the profession.…”
Section: Recommendations For Credentialing and Regulatory Bodiesmentioning
confidence: 99%
“…Clinicians should understand the causes, as well as risk factors of violence and initiate early intervention on admission to prevent violence. Research indicates violence prevention begins the first day a patient is admitted with an effective risk assessment [26][27][28].…”
Section: Patient Factors Admission Risk Assessment For Safetymentioning
confidence: 99%